Prevalence of gastrointestinal helminth parasites of equines in central zone of Kashmir Valley - MARIA, A; SHAHARDAR, R A; BUSHRA, M (The Indian Journal of Animal Sciences, 2012)
Faecal samples (550) from equines were examined in central zone of Kashmir valley from September 2009 to July 2010 and 95.09% were found positive for ova of one or other gastrointestinal helminths. Nematodes were most prevalent helminths (95.09%) followed by cestodes (1.45%). Among nematodes Cyathostomes were found to be the most prevalent (94.72%), followed by Strongylus spp.(81.09%), Triodontophorus spp. (60.90%), Dictyocaulus arnfieldi (13.09%), Oxyuris equi (8.18%), Strongyloides westeri (6.90%) and Parascaris equorum (4.36%). The seasonal analysis exhibited highest infection (100%) in spring followed by 99% in summer, 94.66% in autumn and 88% in winter with nonsignificant variation. The overall prevalence of mixed infection was 91.45%. The overall mean intensity of infection was 1546.45±345.47. Highest mean intensity was recorded in spring followed by autumn summer and minimum in winter. There was nonsignificant variation in incidence and intensity of infection among different types of equines. Similarly, incidence and intensity of infection remained marginally higher in young ones and in females. Different genera of strongyle worms identified on coproculture were Cyathostomum spp. (62.00%) followed by Triodontophorus spp. (8.00%), Gyalocephalus spp. (7.33%), Strongylus vulgaris (6.00%), Strongylus edentatus (4.00%), Trichostrongylus axei (4.00%), Poteriostomum spp. (3.00%) and Oesophagodontus spp. (3.00%).